2021
DOI: 10.21775/cimb.040.049
|View full text |Cite
|
Sign up to set email alerts
|

Complex Oligosaccharide Utilization Pathways in Lactobacillus

Abstract: Lactobacillus is the bacterial genus that contains the highest number of characterized probiotics. Lactobacilli in general can utilize a great variety of carbohydrates. This characteristic is an essential trait for their survival in highly competitive environments such as the gastrointestinal tract of animals. In particular, the ability of some strains to utilize complex carbohydrates such as milk oligosaccharides as well as their precursor monosaccharides, confer upon lactobacilli a competitive advantage. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 164 publications
(235 reference statements)
0
31
0
Order By: Relevance
“…So, increased Lactobacillus has a therapeutic role. Furthermore, increased Lactobacillus and Treponema are nonpathogenic, carbohydrate-metabolizing bacteria that can enhance the supply of nutrients needed in response to GIN infection (Flint et al, 2012;Allison et al, 2018;Zúiga et al, 2020). In addition, KEGG pathways related to carbohydrate metabolism were enhanced in infected lambs.…”
Section: Microbiota Compositionmentioning
confidence: 99%
“…So, increased Lactobacillus has a therapeutic role. Furthermore, increased Lactobacillus and Treponema are nonpathogenic, carbohydrate-metabolizing bacteria that can enhance the supply of nutrients needed in response to GIN infection (Flint et al, 2012;Allison et al, 2018;Zúiga et al, 2020). In addition, KEGG pathways related to carbohydrate metabolism were enhanced in infected lambs.…”
Section: Microbiota Compositionmentioning
confidence: 99%
“…pseudomesenteroides DSM 20193 harbours only a phospho-β-glucosidases cellobioseassociated PTS system within the same operon suggesting a wider specificity of this transporter. In fact, previous studies demonstrated that generic β-glucoside PTS are essential for L. plantarum growth on fructooligosaccharides suggesting a wider specificity beyond β-glucosides [49,50]. Notably, degradation of β-fructosides caused an upregulation of pbg10 gene [51].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the structure of these maltodextrin-utilization gene clusters in LAB has been reviewed in a recent research. 37 Thus, as a mixture of gluco -oligosaccharides, two permeases probably transported LJGO into cells. Thereafter, the α-(1→4)-linked glucose units were binned to a specific maltose/maltodextrin-binding protein, and later decomposed by a local intracellular α-1,4-glucosidase for further catabolism.…”
Section: Discussionmentioning
confidence: 98%